KEPEMIMPINAN KEPALA ADMINISTRASI DALAM MENINGKATKAN KINERJA TENAGA ADMINISTRASI SEKOLAH MENENGAH PERTAMA - Suhartina, Suhartina (Universitas Bandar Lampung (UBL), 2023)
This research has a background in the formulation of the problem of how the leadership of the head of administration in improving the performance of administrative staff and the inhibiting aspects at the Ar-Raihan Integrated Islamic Junior High School (SMP) Bandar Lampung, where leadership is very instrumental in the performance of an organization while this research is descriptive research analyzed through qualitative methods. The research results show that the head of administration in carrying out his leadership has been able to carry out aspects of leadership to support performance but is still hampered by several aspects namely transparency, communication, leadership and personality of all administrative staff resources